Seroprevalence of Hepatitis A and E virus Antibodies in Dhanusha, Madhesh Province, Nepal - Rimal, Sandesh; Shrestha, Sabin; Khadka, Aashma; Matsuda, Mami; Suzuki, Ryosuke; Dumre, Shyam Prakash; Pandey, Basu Dev (Japanese journal of infectious diseases, 2025)
Hepatitis A virus (HAV) and hepatitis E virus (HEV) are believed to have similar routes of transmission and epidemiology in developing countries. This study investigated the seroprevalence of these pathogens among healthy individuals from the Dhanusha district of Madhesh Province, Nepal. Ninety serum samples collected between 2022 and 2023 were analyzed using enzyme-linked immunosorbent assay to detect immunoglobulin (Ig) G antibodies against HAV and HEV. Participants (median age, 23 years; range, 1-45 years) were categorized into five age groups: 1-10, 11-20, 21-30, 31-40, and 41-45 years. The prevalence of HAV and HEV IgG was 96.7% and 13.3%, respectively. All age groups showed high positivity rates for HAV antibodies. In contrast, HEV infection rates were extremely low in children but rapidly increased in adults aged >31 years. No significant correlation was observed between HAV and HEV seropositivity rates. Additional studies, including those in other areas of Nepal, are required for the nationwide serosurveillance of HAV and HEV.